Improving the Interpersonal Relationship among Employees in Nestle - Lee, Soo Pei; Kee, Daisy Mui Hung; Lee, Pei Sin; Chin, Wei San; Gan, Hooi Ming; Alghanim, Bareeq; Kumar, Bablu (Journal of The Community Development in Asia, 2020)
An interpersonal relationship is one of the important social factors that would influence the smoothness of operation within the department that leads to the success of an organization. Productivity increases when individuals work in groups as compared to an individual who works alone. The paper proposes that the interaction among co-workers is important to increase productivity in an organization. Nestle, the world's largest food and beverage company, has the most influential and significant brands around the world. Nestle begins in 1866 with the foundation of the Anglo-Swiss Condensed Milk Company by Henri Nestle. The implications of the study as well as suggestions for future studies are discussed.